The Effect of Fixed Force Exercises by Using Different Tools in the Values of Some Bio Kinematics Variables to the Hit/Spike Skill in Volleyball for Young People (Medico Legal Update, 2020)
The muscular training by adopting fixed foundations is a modern training methods which is concernedwith the development of muscle strength, in fullest stretch This is due to the quality of the exercises thatselected and designed according to the requirements of skill performance which performance is subject toa set of variables that determine the characteristics of this technical performance of the hit/spike skill, itcauses production of the kinetic system, needed by good skill performance as well as the appropriate correctcompatibility that occurs between the variability in the kinematic and kinetic variables determined by thestress used is the best way to success performance as well as the stabilization and orientation of musclegroups to serve skill performance, so the researchers used the experimental method using experimentaldesign of one group appropriate to the nature of the research, the The study sample was chosen by theresearchers in purposive method, numbering 6 athletes, The researchers were keen to apply the stationarystrength training using different tools for the purpose of some Bio kinematics indicators and the developmentof muscle strength for sample members (8) weeks and included (24) training units (3) units per week, Theresults of the research was the most important that all the exercises used to develop the fixed force, whetherthe muscles of the legs, torso or arms, increased the efficiency of the internal force, the strength of ligamentsin the production of torque force.